LEGAL LIABILITY FOR VIOLATION OF ELECTION LAW - KOVBAS, IGOR (Ehrlich’s Journal, 2024)
Abstract. The article is devoted to the study of certain theoretical and legal aspects of legal responsibility for violations of election legislation, substantiating the specifics of legal responsibility for violations of the election rights of citizens. It has been established that the protection of constitutional rights and freedoms of individuals and citizens holds fundamental significance in the hierarchy of values, alongside life, health, liberty, honor, and personal dignity. It has been proven that the relevance of the study of the peculiarities of legal responsibility for violation of election legislation is due to the fact that Ukraine is on the way to building a democratic legal state and the realization by citizens of their constitutional rights to elect and be elected to state authorities and local self-government bodies is of particular importance. The author believes that a significant place in the system of public legal protection of citizens’ electoral rights belongs precisely to the norms of constitutional, administrative and criminal law, since the violation of these rights calls into question the legitimacy of public power in Ukraine. The author proves that the legal responsibility established by law for violation of the election legislation is an important guarantee of the real exercise of the popular will. According to the author, in Ukraine there is an extensive system of legal liability for violations of election legislation: criminal, administrative, constitutional, civil, disciplinary liability. It is argued that the specificity of legal liability for violations of Ukraine’s electoral legislation lies in the fact that, despite the various types of liability, they share a common general object of violations. This object is the constitutional and derivative legal capabilities of citizens to participate in addressing national and local issues by electing their representatives based on individual expression of will.